An Exploratory Study of Rural Parents' Knowledge and Attitudes About HPV Vaccination Following a Healthcare Visit With Their Child's Primary Care Provider - Caitlin Dickinson; Sarah Bumatay; Steele Valenzuela; Brigit A. Hatch; Patricia A. Carney (SAGE Publishing, 2023)
Introduction/Objectives: Annually, HPV infections result in $775 million in direct medical costs and approximately 46 000 new cases of HPV-associated cancers. Safe and highly effective vaccines have been available to prevent HPV for children/adolescents since 2006. Vaccination rates remain low, especially in rural areas. Parental attitudes and beliefs affect HPV vaccination rates. Methods: We developed, tested, and administered a survey that asked how parents and healthcare providers interacted about the HPV vaccine following a healthcare visit with an age-eligible child, as part of a multicomponent randomized controlled trial designed to improve HPV vaccination rates in rural Oregon. The 21-item survey assessed parents' information-seeking behavior, knowledge about HPV cancer risk reduction, the HPV vaccine series, and their vaccine confidence. Results: Forty-three participants (59.7%) were in the intervention group; 29 (40.3%) were controls. Over 90% of healthcare visits were illness, injury, sports physical, or well-child visits (n = 67 or 93.1%), and 6.9% of visits were vaccine-specific. No statistically significant differences were found between study groups for healthcare visits. Over half the parents reported having discussions about HPV and the HPV vaccine (54.5%) with their care providers, 31.3% had recently learned about HPV, HPV risks, and the HPV vaccine prior to the visit, 83.1% were knowledgeable about cancers associated with HPV, and 79.2% were considering vaccinating their child(ren), which did not differ between study groups. Conclusions: Knowledge about HPV-related cancers and consideration for vaccinating children was higher than expected, but not associated with the intervention tested.